Islamic Philanthropy, Macroeconomics Factors, and Poverty: Panel Data Evidence from Muslim-Majority Provinces in Indonesia - Lestari, Anisa; Putra, Trisca Relanda; Zubaidah, Siti (IJoIS: Indonesian Journal of Islamic Studies, 2026)
Despite Indonesia’s vast zakat potential, empirical gaps remain regarding the consistent impact of Islamic philanthropy and macroeconomic indicators on poverty alleviation, particularly within integrative models covering the post-pandemic phase. This study aims to analyze the determinants of poverty in Indonesia’s Muslim-majority provinces from 2019 to 2023 by integrating Islamic philanthropy, macroeconomics, and socio-demographic variables. Utilizing a quantitative approach with panel data regression, the Fixed Effect Model (FEM) was identified as the optimal model based on the Hausman test. The findings reveal that zakat and economic growth have a significant negative impact on poverty, effectively reducing poverty rates. Conversely, DSKL (Religious Social Funds), mean years of schooling, and social assistance exhibit a significant positive relationship with poverty levels. Meanwhile, infaq, alms, local revenue (PAD), inflation, minimum wage (UMP), and the Human Development Index (HDI) show no significant effect. The primary contribution of this research is providing a comprehensive model proving that poverty reduction requires synergy between productive religious instruments and inclusive fiscal policies. These results imply that the government and zakat institutions must optimize the governance of integrated Islamic philanthropy alongside human capital strengthening to achieve sustainable poverty reduction. These findings highlight the importance of integrating Islamic philanthropy governance with regional fiscal policies and human capital development to achieve sustainable poverty reduction